BMAL1 deficiency promotes skeletal mandibular hypoplasia via OPG downregulation. (17th August 2018) - Zhou, Xin; Yu, Ran; Long, Yanlin; Zhao, Jiajia; Yu, Shaoling; Tang, Qingming; Chen, Lili
Abstract: Objectives: Skeletal mandibular hypoplasia (SMH), a common type of developmental deformities, results in impaired aesthetics of facial profile, occlusal dysfunction and poor life quality. In this study, BMAL1 deficiency leads to SMH formation, and we aim to investigate the mechanism by which BMAL1 deficiency induces SMH. Materials and methods: Circadian rhythm‐disordered mouse models were constructed by placing animals in a jet lag schedule of 6‐h light advance every 7 days for 4 or 8 weeks. The OPG expression was evaluated by histomorphometry, immunohistochemistry and western blot analysis. The mechanism by which BMAL1 affects OPG expression was investigated by chromatin immunoprecipitation and luciferase reporter assays. The phenotypes caused by BMAL1 knockout can be rescued by exogenous supplementation with OPG. Results: We demonstrate that the expressions of BMAL1 and OPG decreased in SMH patients. Circadian rhythm‐disordered mice and Bmal1 −/− mice exhibited decreased expression of OPG, reduced bone mass and bone size of mandibles. Our results revealed that BMAL1 bound directly to the Opg promoter and upregulated its expression, thus inhibiting osteoclast differentiation. BMAL1 deficiency increased osteoclast differentiation by downregulating OPG expression. In vitro, the enhancement effect of osteoclast differentiation caused by BMAL1 knockdown was significantly reversed by exogenous supplementation with OPG. Importantly, bone loss caused by BMAL1 knockout can be partially reversed by injecting OPG Intraperitoneally. Conclusions: These results indicate that the circadian clock plays a critical role in the growth and development of mandible by regulating OPG expression, and present a potential therapeutic strategy to prevent SMH.